Dialogic Reading Sebagai Upaya Mengembangkan Keterampilan Berbahasa Anak Usia Dini - Vina Anggia Nastitie Ariawan; Inne Marthyane Pratiwi (Jurnal Pendidikan Raudhatul Athfal, 2018)
Language skills are basic skills that are mastered and learned early childhood. Language skills obtained by the child through interaction with parents. Early childhood language development periods are categorized into two, namely pre-linguistic and linguistic periods. Pre-linguistic periods are passed by the child as a baby. If in the pre-linguistic period the child is introduced to the proper use of language then the language skills of the child develop in the linguistic period. The intensity of an interaction will affect the skills of listening and speaking of early childhood. Therefore, parents and teachers as a close to the child are very necessary to facilitate the development of the language of children. Dialogic reading is an approach used to develop language skills and basic literacy of children. Dialogic reading provides many opportunities for children to speak so that language skills and self-confidence are growing.